Current Controversies in Large-Vessel Inflammatory Vasculitis and Thoracic Aortic Aneurysm Disease - Harky, Amer; Fok, Matthew; Howard, Callum; Bashir, Mohamad (International Journal of Angiology, 2019)
Large-vessel vasculitis encompasses the spectrum of vasculitides, which pathologically cause chronic granulomatous inflammatory changes, primarily in the aorta and its major branches. These patients are at risk of developing life-threatening aortic lesions that, without recognition and prompt treatment, can cause detrimental effects. Many provocative issues surrounding large-vessel vasculitis and its surgical treatment still remain, spanning from recognition to management. In this review, we discuss the main large-vessel vasculitides, Takayasu's arteritis and giant cell arteritis. We include the key points and current controversies surrounding diagnostic imaging, timing of interventions, and patient outcomes.
Keywords: large vessel; vasculitis; thoracic aortic disease